High-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cable and preparation method thereof
A composite polymer blend with shape-memory microencapsulated red phosphorus and ammonium molybdate enhances flame retardancy and mechanical properties, addressing high-speed extrusion challenges and environmental stability issues in optical cable materials.
Patent Information
- Application Number
- CN202510596848.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-07-15
AI Technical Summary
The existing stretch-stretch optical cable polyolefin sheath material is prone to sticking during high-speed extrusion and has poor surface quality, making it difficult to pass high-standard flame retardant tests, lack of mechanical properties and flexibility, poor long-term environmental stability, and cannot meet the requirements of complex construction and long-term use.
A combination of ethylene-vinyl acetate copolymer, SEBS flame retardant masterbatch, low-density polyethylene, maleic anhydride grafted polyethylene, magnesium hydroxide, synergistic flame retardant, calcium carbonate, antioxidant and lubricant is used, and in particular, a shape memory microencapsulated flame retardant is used as a synergistic flame retardant composite containing red phosphorus and ammonium molybdate, low-smoke halogen-free flame retardant polyolefin materials are prepared through a specific process.
It achieves excellent flame retardant properties, good mechanical properties and flexibility of the material, chemical resistance and weather resistance, meets the requirements of high-speed extrusion process, reduces smoke and toxicity, and improves the thermal stability and service life of the material.
Smart Images

Figure BDA0005394833830000101 
Figure BDA0005394833830000111 
Figure BDA0005394833830000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer material processing, and particularly relates to a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote fiber optic cables and a preparation method thereof. Background Art
[0002] With the continuous development of the information age, people's demand for the network is getting higher and higher. Traditional fiber optic cable communication can no longer meet the market needs. Therefore, remote fiber optic cables have become a necessary solution. By laying an additional fiber optic cable on the basis of the original fiber optic cable, remote fiber optic cables can achieve longer-distance communication transmission and larger communication capacity, making network communication more extensive and reliable.
[0003] Specifically, the existing polyolefin sheath materials for remote fiber optic cables have the following technical problems:
[0004] (1) Processing speed: The existing technology is difficult to meet the processing requirements of high-speed extrusion (≥120 m / min). During high-speed extrusion, the sheath material is prone to problems such as adhesion and poor surface quality, affecting production efficiency and product quality;
[0005] (2) Flame retardant performance: Although some outer sheath materials for remote fiber optic cables have flame retardancy, it is still difficult to pass high-standard flame retardant tests such as IEC 60332-1; to meet the requirements of high flame retardant performance, a large amount of flame retardant is often added, which will reduce the mechanical properties and flexibility of the material;
[0006] (3) Mechanical properties and flexibility: When the dosage of the flame retardant filler exceeds 60%, the mechanical properties (such as tensile strength and elongation at break) of the sheath material decrease significantly, the flexibility becomes poor, and it is easy to break, making it difficult to meet the requirements of complex construction environments and long-term use;
[0007] (4) Long-term environmental stability: In high-temperature and high-humidity environments (such as double 85 tests: temperature 85°C, humidity 85%), the existing sheath materials for remote fiber optic cables are prone to problems such as aging, cracking, and performance degradation, affecting the service life and reliability of the fiber optic cables. Summary of the Invention
[0008] To solve the above technical problems, the purpose of the present invention is to provide a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote fiber optic cables and a preparation method thereof; the high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote fiber optic cables has excellent flame retardant performance, good mechanical properties and flexibility, as well as excellent chemical resistance and weather resistance, and can meet the requirements of high-speed extrusion processes.
[0009] To achieve the above technical purposes and reach the above technical effects, the present invention is realized through the following technical solutions:
[0010] On the one hand, the present invention provides a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables, which comprises the following raw materials according to weight ratio: 15-30 parts of ethylene-vinyl acetate copolymer, 5-8 parts of SEBS flame-retardant masterbatch, 8-11 parts of low-density polyethylene, 5-8 parts of maleic anhydride grafted polyethylene, 5-10 parts of magnesium hydroxide, 1-3 parts of synergistic flame retardant, 30-45 parts of calcium carbonate, 0.1-0.5 parts of antioxidant, and 1-2 parts of lubricant; the synergistic flame retardant is a shape memory microencapsulated flame retardant, and its core material is a flame-retardant compound containing red phosphorus and ammonium molybdate.
[0011] Further, the VA content in the ethylene-vinyl acetate copolymer is 15-20%.
[0012] Further, the SEBS flame-retardant masterbatch is prepared from calcium carbonate, silane coupling agent, white oil, melamine polyphosphate, SEBS particles, and polyethylene according to the mass ratio of 60:1:1:5:20:15.
[0013] Preferably, the antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and thioester antioxidants.
[0014] Preferably, the lubricant is compounded from an internal lubricant and an external lubricant, wherein the internal lubricant is selected from at least one of zinc stearate, calcium stearate, stearic acid, and fatty alcohol, and the external lubricant is selected from at least one of paraffin wax, microcrystalline wax, polyethylene wax, and silicone.
[0015] Further, the wall material of the shape memory microencapsulated flame retardant is a multi-layer structure, including a polyurethane wall material in the inner layer and an alumina coating in the outer layer.
[0016] Further, the preparation method of the shape memory microencapsulated flame retardant is as follows:
[0017] (1) Dispersing the flame-retardant compound particles in a polyurethane solution, adding appropriate amounts of emulsifier and dispersant, and making them evenly distributed by high-speed stirring or ultrasonic dispersion; placing the dispersed mixture in a spray dryer for spray drying to obtain polyurethane microencapsulated flame retardant;
[0018] (2) Dispersing the polyurethane microencapsulated flame retardant in the pre-prepared alumina gel, stirring, and then vacuum drying the microcapsules immersed in the alumina gel to obtain the shape memory microencapsulated flame retardant.
[0019] On the other hand, the present invention provides a preparation method of a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables, which comprises the following steps:
[0020] (1) Mix ethylene-vinyl acetate copolymer, SEBS flame retardant masterbatch, low-density polyethylene, maleic anhydride grafted polyethylene, magnesium hydroxide, synergistic flame retardant, calcium carbonate, antioxidant and lubricant in a mixer.
[0021] (2) Melt and blend the mixed material obtained in step (1) through a twin-screw extruder, and granulate by face cutting with hot air.
[0022] (3) Feed the granules obtained in step (2) into a single-screw extruder and extrude at high speed, and then shape and set by air cooling.
[0023] Further, in step (1), the mixing temperature of the mixer is 120 - 150 °C.
[0024] Further, in step (2), the temperature range of the twin-screw extruder is 160 - 190 °C.
[0025] The beneficial effects of the present invention are as follows:
[0026] (1) The present invention contains magnesium hydroxide and a synergistic flame retardant, wherein the synergistic flame retardant is a shape memory microencapsulated flame retardant, and its core material is a flame retardant compound containing red phosphorus and ammonium molybdate; the three of magnesium hydroxide, red phosphorus, and ammonium molybdate act synergistically to significantly improve the flame retardant effect, specifically as follows:
[0027] When red phosphorus is heated, it decomposes to generate phosphorus-containing compounds such as phosphoric acid, promoting the dehydration and carbonization of organic materials to form a dense carbon layer; magnesium hydroxide decomposes at 340 °C - 492 °C to generate substances such as magnesium oxide, and these substances fill into the carbon layer, enhancing the stability and density of the carbon layer; the molybdenum-containing active substances generated by the decomposition of ammonium molybdate can also promote the carbonization reaction, further improving the quality of the carbon layer. The combined action of the three makes the carbon layer thicker and stronger, and can more effectively isolate oxygen and heat, preventing the material from burning;
[0028] The thermal decomposition temperature range of red phosphorus is relatively wide (about 200 °C to 500 °C), the thermal decomposition temperature of magnesium hydroxide is relatively high and it has a good heat absorption effect (340 °C - 492 °C), and ammonium molybdate decomposes at a higher temperature and releases active free radicals. They play heat absorption and flame retardant roles at different temperature stages, enabling the flame retardant system to effectively inhibit the thermal decomposition of materials within a relatively wide temperature range and improving the thermal stability of materials;
[0029] The gaseous substances such as phosphorus oxides generated by the decomposition of red phosphorus and molybdenum oxides generated by the decomposition of ammonium molybdate can capture free radicals in the combustion reaction in the gas phase, interrupting the combustion chain reaction. The synergistic effect of the two can more effectively inhibit the propagation and spread of the flame;
[0030] The water vapor generated by the decomposition of magnesium hydroxide can dilute the combustible gases generated by the decomposition of the material, reduce the flame temperature and reaction rate. At the same time, phosphorus oxides and molybdenum oxides can also dilute the combustible gases to a certain extent, further reducing the combustion intensity.
[0031] Red phosphorus and its decomposition products can inhibit the smoke generated during the combustion of the material. The water vapor generated by the decomposition of magnesium hydroxide can dilute the smoke particles. Ammonium molybdate has a significant smoke suppression effect, which can reduce the concentration and toxicity of the smoke. The compounding of the three can significantly reduce the smoke volume and flue gas toxicity during the combustion of the material.
[0032] (2) The synergistic flame retardancy of magnesium hydroxide and the synergistic flame retardant can reduce the dosage of magnesium hydroxide and ensure good mechanical properties and flexibility.
[0033] (3) The synergistic flame retardant in the present invention is a shape memory microcapsule flame retardant; the specific effects are as follows:
[0034] In the present invention, a shape memory polymer is used as the wall material to encapsulate the compound of red phosphorus and ammonium molybdate. At room temperature, the wall material blocks the compound from the external environment, preventing it from absorbing moisture, oxidizing, and releasing toxic gases, maintaining its chemical stability and flame retardant properties, ensuring that the flame retardant compound can be effectively released and play a role when needed, and also improving the compatibility of the flame retardant compound with the polymer material, making it easier to disperse. When the temperature reaches the transition temperature of the wall material, the wall material softens or melts, and the flame retardant compound is released to play a flame retardant role. In addition, when the fire source is extinguished or the temperature drops, the shape memory polymer wall material can re-solidify to prevent further release of the flame retardant compound, avoid excessive release of the flame retardant compound, ensure that it can still play a flame retardant role in the subsequent possible reappearance of the fire source or high temperature situation, improve the use efficiency and durability of the flame retardant, and avoid the internal structure change of the material that may be caused by excessive release, and avoid affecting the mechanical properties and other physical and chemical properties of the material.
[0035] In the present invention, the wall material of the shape memory microencapsulated flame retardant has a multi-layer structure, which includes a polyurethane wall material located in the inner layer and an alumina coating located in the outer layer. The multi-layer wall material structure can provide a more stable release platform. The polyurethane wall material begins to soften when it reaches its glass transition temperature, and the flame retardant compound is gradually released and participates in the flame retardant reaction; the alumina coating provides thermal insulation protection at high temperatures, slowing down the heat transfer to the inner layer, which enables the polyurethane wall material to delay the response to temperature changes before reaching its Tg, ensuring that the flame retardant compound is released within a suitable time and temperature range, and avoiding its premature or late action. In addition, the alumina coating can adsorb and solidify the harmful gases generated during the combustion process to a certain extent, reducing their diffusion into the atmosphere.
[0036] (4) The present invention also contains an SEBS flame retardant masterbatch. The SEBS therein can resist the erosion of various chemicals and ultraviolet radiation, and has excellent chemical and weather resistance. The melamine polyphosphate therein improves the flame retardancy and thermal stability of the material by promoting char formation, releasing inert gases, diluting smoke, and absorbing heat to lower the temperature. Detailed implementation manners
[0037] The technical solutions in the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0038] The present invention provides a high-speed extrusion low-smoke halogen-free flame retardant polyolefin material for remote optical cables, which includes the following raw materials according to weight ratio: 15-30 parts of ethylene-vinyl acetate copolymer, 5-8 parts of SEBS flame retardant masterbatch, 8-11 parts of low-density polyethylene, 5-8 parts of maleic anhydride grafted polyethylene, 5-10 parts of magnesium hydroxide, 1-3 parts of synergistic flame retardant, 30-45 parts of calcium carbonate, 0.1-0.5 parts of antioxidant, and 1-2 parts of lubricant; the synergistic flame retardant is a shape memory microencapsulated flame retardant, and its core material is a flame retardant compound containing red phosphorus and ammonium molybdate.
[0039] Among them, the VA content in the ethylene-vinyl acetate copolymer is 15-20%.
[0040] Among them, the SEBS flame retardant masterbatch is prepared from calcium carbonate, silane coupling agent, white oil, melamine polyphosphate, SEBS particles, and polyethylene as raw materials according to a mass ratio of 60:1:1:5:20:15. The specific preparation method is as follows:
[0041] Pretreatment: Dry the SEBS particles in an oven at 60-80 °C for 4-6 hours to avoid generating bubbles during processing; dry the melamine polyphosphate at 100-120 °C for 2-4 hours to remove moisture and prevent pores caused by volatile components during processing;
[0042] Processing and pelletizing: Feed into a 75L internal mixer according to the ratio and order of calcium carbonate: silane coupling agent: 26# white oil: melamine polyphosphate: SEBS particles: polyethylene = 60:1:1:5:20:15, and pelletize under the process conditions of an internal mixing temperature of 180 °C and a single-screw temperature of 120 °C / 130 °C / 140 °C / 150 °C / 160 °C.
[0043] Among them, the antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and thioester antioxidants.
[0044] Among them, the lubricant is compounded by an internal lubricant and an external lubricant. The internal lubricant is selected from at least one of zinc stearate, calcium stearate, stearic acid, and fatty alcohol, and the external lubricant is selected from at least one of paraffin wax, microcrystalline wax, polyethylene wax, and silicone. The cooperation of the internal lubricant and the external lubricant can reduce the friction between molecular chains, lower the melt viscosity, reduce the adhesion between the melt and the screw, lower the screw extrusion pressure, reduce the material extrusion current, and improve the material processing performance.
[0045] Among them, the wall material of the shape memory microencapsulated red phosphorus is a multi-layer structure, including a polyurethane wall material in the inner layer and an alumina coating in the outer layer. The preparation method of the shape memory microencapsulated red phosphorus is specifically as follows:
[0046] (1) Mixing and pretreatment
[0047] Put red phosphorus and ammonium molybdate particles (the proportion of ammonium molybdate particles in the total amount of particulate matter is 2%-3%) into a ball mill for ball milling, and the ball milling time is 2-3 hours; wash the ball-milled mixed particulate matter with an organic solvent to remove surface impurities and dust, and then dry it to constant weight in a vacuum drying oven.
[0048] (2) Preparation of polyurethane wall material solution
[0049] Mix the polyurethane prepolymer and the curing agent in a certain proportion, stir evenly, add an appropriate amount of solvent (such as toluene or xylene) to adjust the viscosity of the solution, the stirring speed is 300-500 revolutions per minute, and the stirring time is 30-60 minutes; let the mixed polyurethane solution stand and cure at room temperature, and the curing time is 2-24 hours.
[0050] (3) Formation of microcapsules
[0051] Disperse the pretreated mixed particulate matter in the prepared polyurethane solution above. The mass ratio of the polyurethane solution to the mixed particulate matter is (1-3):1, then add an appropriate amount of emulsifier and dispersant, and make it evenly distributed by high-speed stirring or ultrasonic dispersion; the stirring speed is 1000-2000 revolutions per minute, and the stirring time is 30-60 minutes; the ultrasonic dispersion time can be 10-30 minutes;
[0052] Put the dispersed mixed liquid into a spray dryer for spray drying, the inlet air temperature is 150-200°C, the outlet air temperature is 80-100°C, the feeding speed is determined according to the viscosity of the mixed liquid and the performance of the spray dryer, and collect the polyurethane microencapsulated flame retardant.
[0053] (4) Preparation of alumina gel
[0054] Dissolve an aluminum salt (such as aluminum sulfate or aluminum nitrate) in water and stir until completely dissolved to form an aluminum salt solution. Then slowly add an alkali solution (such as ammonia water or sodium hydroxide solution) for a neutralization reaction, controlling the pH value between 8 and 10. Stir continuously during the reaction to ensure uniform progress of the reaction. The reaction time is 2 to 4 hours. Let the generated alumina gel stand and age at room temperature for 24 to 72 hours to improve the stability of the gel.
[0055] (5) Immerse in the alumina gel
[0056] Disperse the polyurethane microencapsulated flame retardant in the prepared alumina gel to ensure that the surface of the microcapsules is uniformly covered by the alumina gel. Stir with a magnetic stirrer at a stirring speed of 300 - 500 revolutions per minute for 30 - 60 minutes. Dry the microcapsules immersed in the alumina gel in a vacuum drying oven at 60 - 80 °C to remove moisture and cure the alumina gel to form a dense alumina coating. The drying time is 12 - 24 hours.
[0057] (5) Post-treatment
[0058] Filter or centrifuge the dried microcapsules to remove the alumina particles not adsorbed on the surface of the microcapsules. Finally, store the microcapsules in a dryer to prevent moisture absorption and contamination.
[0059] The preparation method of the high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for the remote fiber optic cable includes the following steps:
[0060] (1) Mix ethylene-vinyl acetate copolymer, SEBS flame retardant masterbatch, low-density polyethylene, maleic anhydride grafted polyethylene, magnesium hydroxide, synergistic flame retardant, calcium carbonate, antioxidant and lubricant in a mixer. In step (1), the mixing temperature of the mixer is 120 - 150 °C and the mixing time is 15 - 20 minutes.
[0061] (2) Melt-blend and extrude the mixed material obtained in step (1) through a twin-screw extruder and cut it into pellets by hot cutting on the die face. The temperature range of the twin-screw extruder is 160 - 190 °C.
[0062] (3) Feed the pellets obtained in step (2) into a single-screw extruder for high-speed extrusion and then shape them by air cooling. The temperature of the single-screw extruder is set at 180 °C and the screw speed is 150 r / min.
[0063] The present invention will be further described in detail through specific embodiments below.
[0064] Example 1
[0065] The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables in Example 1 includes the following raw materials according to the weight ratio: 20 parts of ethylene-vinyl acetate copolymer, 6 parts of SEBS flame-retardant masterbatch, 11 parts of low-density polyethylene, 5 parts of maleic anhydride-grafted polyethylene, 5 parts of magnesium hydroxide, 1.5 parts of synergistic flame retardant, 42 parts of calcium carbonate, 0.4 parts of antioxidant, and 1.8 parts of lubricant; the synergistic flame retardant is a shape-memory microencapsulated flame retardant, and its core material is a flame-retardant compound containing red phosphorus and ammonium molybdate. In Example 1, ammonium molybdate accounts for 2% of the total amount of the flame-retardant compound; the lubricant is compounded by stearic acid and silicone in a mass ratio of 1:2; the antioxidant is compounded by antioxidant 1010, dilauryl thiodipropionate DLTP, and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1:1.
[0066] The preparation method of the high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables in Example 1 includes the following steps:
[0067] (1) Mix ethylene-vinyl acetate copolymer, SEBS flame-retardant masterbatch, low-density polyethylene, maleic anhydride-grafted polyethylene, magnesium hydroxide, synergistic flame retardant, calcium carbonate, antioxidant, and lubricant in a mixer; in step (1), the mixing temperature of the mixer is 140 °C, and the mixing time is 20 minutes;
[0068] (2) Melt and blend the mixed material obtained in step (1) through a twin-screw extruder and granulate by face cutting; the temperature range of the twin-screw extruder is 160-190 °C;
[0069] (3) Put the pellets obtained in step (2) into a single-screw extruder for high-speed extrusion granulation, and then shape and set them by air cooling. The temperature of the single-screw extruder is set at 180 °C, and the screw speed is 150 r / min.
[0070] Prepare the sheath materials of other examples and comparative examples according to the component weight ratio (parts) in Table 1 below.
[0071] Table 1
[0072]
[0073]
[0074] The SEBS flame-retardant masterbatch, shape-memory microencapsulated flame retardant, antioxidant, internal lubricant, and external lubricant in Table 1 are the same as those in Example 1.
[0075] The process conditions of the preparation methods of Example 2, Example 3, and the comparative example are the same as those in Example 1.
[0076] Perform performance tests on the sheath materials of Examples 1-3 and the comparative examples; the performance test methods are as follows:
[0077] Sample preparation: First, weigh each component according to the ratio and add them to the internal mixer platform of the rheometer. Set the temperature to 150°C / 150°C / 150°C, the rotation speed to 50 revolutions per minute, and start internal mixing. After the torque becomes stable, take out the material. Secondly, use a two-roll mill for open mixing, and the mixed material should be smooth and bubble-free. Then preheat it in a flat vulcanizing machine with a pressure of 18±2 MPa for 5 minutes, apply pressure at 170±5°C for 5 minutes, and cool and apply pressure for 5 minutes to obtain a sample sheet. Then conduct tests according to the test items.
[0078] Test methods:
[0079] Double 85 test: Under the condition that the environment is set to a temperature of 85°C and a humidity of 85%, conduct an aging test on the test body. This test method evaluates the performance and reliability of the product under extreme conditions by simulating a high-temperature and high-humidity environment. Usually, the test time is set to 1000 hours or longer to examine the limit that the product can withstand when exposed to a high-temperature and high-humidity environment for a long time.
[0080] Single wire burning test: Vertically install the specimen on the bracket, align the center of the burner with the lower surface of the specimen, and the axis of the burner forms a 45-degree angle with the axis of the specimen; light the burner and adjust the flame height to the specified value, and start timing; after continuous burning for 60 seconds, turn off the burner and immediately record the carbonization situation of the specimen; observe the afterflame time and calculate the carbonization length starting from the moment the flame goes out. It is mainly used to test the ability of a single cable or insulating material to resist flame spread in a vertical state.
[0081] Light transmittance test: The light transmittance of a cable refers to the ability of the cable to allow light to penetrate when irradiated with light. Specifically, the light transmittance refers to the proportion of light passing through the cable sheath material, usually expressed as a percentage of light transmittance. Test according to IEC61034-2 standard.
[0082] The performance test results of Examples 1-3 and the comparative examples are shown in Table 2.
[0083] Table 2
[0084]
[0085] As can be seen from Table 2 above, the polyolefin sheath materials of the embodiments of the present invention have excellent flame retardancy, good mechanical properties, excellent chemical resistance and weather resistance, and can meet the requirements of high-speed extrusion processes.
[0086] It is obvious to those skilled in the art that the present invention is not limited to the details of the above-described exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, in any respect, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be embraced within the present invention.
[0087] In addition, it should be understood that although this specification is described in terms of embodiments, not every embodiment only contains an independent technical solution. This narrative style of the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A high-speed extruded low-smoke, halogen-free, flame-retardant polyolefin material for remote optical cables, characterized in that, It comprises the following raw materials according to the weight ratio: 15 - 30 parts of ethylene-vinyl acetate copolymer, 5 - 8 parts of SEBS flame retardant masterbatch, 8 - 11 parts of low-density polyethylene, 5 - 8 parts of maleic anhydride grafted polyethylene, 5 - 10 parts of magnesium hydroxide, 1 - 3 parts of synergistic flame retardant, 30 - 45 parts of calcium carbonate, 0.1 - 0.5 parts of antioxidant, 1 - 2 parts of lubricant; the synergistic flame retardant is a shape memory microencapsulated flame retardant, and its core material is a flame retardant compound containing red phosphorus and ammonium molybdate.
2. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 1, wherein The VA content in the ethylene-vinyl acetate copolymer is 15 - 20%.
3. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 1, characterized in that The SEBS flame retardant masterbatch is prepared from calcium carbonate, silane coupling agent, white oil, melamine polyphosphate, SEBS particles, and polyethylene according to the mass ratio of 60:1:1:5:20:
15.
4. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 1, wherein The antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and thioester antioxidants.
5. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 1, characterized in that, The lubricant is compounded from internal lubricant and external lubricant. Among them, the internal lubricant is selected from at least one of zinc stearate, calcium stearate, stearic acid, and fatty alcohol, and the external lubricant is selected from at least one of paraffin wax, microcrystalline wax, polyethylene wax, and silicone.
6. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 1, wherein The wall material of the shape memory microencapsulated flame retardant is a multi-layer structure, including a polyurethane wall material in the inner layer and an alumina coating in the outer layer.
7. The high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 6, wherein, The preparation method of the shape memory microencapsulated flame retardant is as follows: (1) Disperse the flame retardant compound particles in a polyurethane solution, add an appropriate amount of emulsifier and dispersant, and make it evenly distributed by high-speed stirring or ultrasonic dispersion; place the dispersed mixture in a spray dryer for spray drying to obtain polyurethane microencapsulated flame retardant; (2) Disperse the polyurethane microencapsulated flame retardant in the pre-prepared alumina gel, stir, and then vacuum dry the microcapsules immersed in the alumina gel to obtain the shape memory microencapsulated flame retardant.
8. A preparation method of a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for remote optical cables, characterized in that, It includes the following steps: (1) Mix ethylene-vinyl acetate copolymer, SEBS flame retardant masterbatch, low-density polyethylene, maleic anhydride grafted polyethylene, magnesium hydroxide, synergistic flame retardant, calcium carbonate, antioxidant, and lubricant in a mixer; (2) Melt and co-extrude the mixed material obtained in step (1) through a twin-screw extruder, and cut it into pellets by face cutting; (3) Put the pellets obtained in step (2) into a single-screw extruder for high-speed extrusion, and then shape it by air cooling.
9. The preparation method of a high-speed extruded low-smoke halogen-free flame-retardant polyolefin material for remote optical cables according to claim 8, characterized in that, In step (1), the mixing temperature of the mixer is 120 - 150 °C.
10. The preparation method of a high-speed extrusion low-smoke halogen-free flame-retardant polyolefin material for a remote optical cable according to claim 8, characterized in that, In step (2), the temperature range of the twin-screw extruder is 160 - 190 °C.
Citation Information
Cited By
B1-grade cable insulating material for home decoration and preparation method thereof
CN121086393A